Modeling of coupling coefficient as a function of coupling ratio - Toto, Saktioto (Versita Publications, 2008)

(untitled)
Coupled 1X2 Single Mode Fiber (SMF-28eÂ®) has been successfully fabricated using a slightly unstable torch flame at a temperature range of 800oC to 1350oC injecting hydrogen gas flowing at pressure of 1 bar. The coupling ratio and coupling coefficient can be examined from 1% until 75%. In this paper, we compare the experimental results by using a simple kinetic model of coupling coefficient where internal and external parametric functions are considered. This equation is time independent and is then integrated over the coupling ratio range for various separation fibers axis between two cores. The result shows that the separation between the cores significantly affects coupling coefficient exhibiting exponential behavior. In this experiment the coupling coefficient gradient is significantly changed towards the coupling ratio but in modeling it has a function of separation fiber axis and no power imposed. These phenomena will determine the effects of power losses at coupling region where fabrications of coupled fibers are demonstrated.